The growth of the post-war public expenditure state: long-term trajectories and recent trends - Francis G. Castles (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
This Working Paper has two principal objectives. The first is to describe the main trajectories of development of public expenditure aggregates in OECD countries during the period 1960-2001. The second is to provide a more detailed analysis of expenditure trends in these countries in the period since 1980, with a view to establishing the extent and sources of expenditure retrenchment in this latter period. The aggregates examined include total outlays of general government, total social expenditure and the core spending of general government, including expenditures on defence, public order, education, general public services, economic affairs, community services and environmental protection. The headline stories of the general survey of expenditure trajectories include the massive overall expansion of public spending, the declining importance of military expenditures and the increased salience of spending on social policy objectives and, most recently, a shift within the latter category from cash benefit spending to spending on service provision. Significant findings of the analysis of trends include the pronounced convergence of aggregate expenditure levels, the role of slow economic growth in promoting the measured growth of public expenditure and the continuing importance of the partisan complexion of government in shaping spending patterns. The analysis also suggests that post-1980 retrenchment tendencies were restricted to core spending, were only marginally influenced by developments in the global economy and were driven almost entirely by a conjuncture of high levels of public indebtedness and high real interest rates which is unlikely to be repeated in the near future.
Keywords: 330; Öffentliche Ausgaben; Staatsquote; OECD-Staaten